Analyzing process flow of autoclaves stations for canned food processing to balance and synchronize them with production lines - Arteaga Irene, Yober Arteaga (2018)
Even though there are many techniques available for optimizing operations in a manufacturing environment, it is a challenge to create and optimize flow on the shop floor. In the canning food industry safety issues are foremost so most of the variables related to time are fixed such as in autoclaves stations in which the product can only wait up to a specific time (maximum retention time) to be processed and the thermal treatment times are set values for each type of product. This study analysed the process flow of autoclaves stations, formulated a mathematical model for buffer allocation and developed a software application in NetBeans IDE 8.2.